Cost variation analysis of commonly prescribed oral antipsychotic drugs available in India-a pharmacoeconomic perspective - R., Nivetha Raj; A., Geetha (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Antipsychotics are commonly prescribed for a variety of psychiatric disorders which require prolonged treatment. If a costly brand is prescribed, it reduces patient compliance, especially in the lower socio-economic groups. Awareness about the cost variation among different brands will guide an economically effective prescription by the treating physician. Methods: The cost of different brands of commonly used oral antipsychotic drugs available in the Indian market manufactured by different companies, in the same strength, number and dosage form was obtained from the latest CIMS, MIMS, and India drug Index. The cost ratio and percentage cost variation were calculated for each. The cost for the same drugs was also noted from the Jan Aushadhi generic medicines portal and a comparison was made. Results: The percentage variation in the cost was above 100% with most of the commonly used antipsychotic drugs like haloperidol (517%), trifluoperazine (504.12%), risperidone (485.27%), chlorpromazine (436.35%), aripiprazole (340.34%), flupenthixol (293.12%), olanzapine (245%), ziprasidone (176.02%), amisulpride (169.44%), quetiapine (163.16%). Percentage cost variation between branded and generic drugs ranged from 400-1050%. Conclusions: There is substantial cost variation among the various brands of antipsychotic drugs. Stigma surrounding generic prescription needs to be addressed. More psychiatric drugs need to be included under National list of essential medicines and DPCO (Drug price control order) so that there can be a ceiling on the maximum price.